2021
DOI: 10.1523/eneuro.0110-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Glutamatergic Drive Underlie Diverse Responses of Olfactory Bulb OutputsIn Vivo

Abstract: Mitral/tufted (MT) cells of the olfactory bulb (OB) show diverse temporal responses to odorant stimulation that are thought to encode odor information. Much of this diversity is thought to arise from inhibitory OB circuits, but the dynamics of excitatory input to MT cells, which is driven in a feedforward manner by sensory afferents, may also be important. To examine the contribution of excitatory input dynamics to generating temporal diversity in MT cells, we imaged glutamate signaling onto MT cell dendrites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 76 publications
(115 reference statements)
1
27
0
Order By: Relevance
“…Clearly, olfactory receptor neurons exhibit synaptic depression under some conditions, which would be transmitted to the mitral/tufted cells. The relative proportion of mitral/tufted cell adaptation that can be attributed to depression at the olfactory receptor neuron synapse needs to be addressed in future work using either sensors of synaptic vesicle release ( Bozza et al, 2004 ; Wachowiak et al, 2005 ) or glutamate targeted to postsynaptic neurons ( Marvin et al, 2013 , 2018 ; Moran et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, olfactory receptor neurons exhibit synaptic depression under some conditions, which would be transmitted to the mitral/tufted cells. The relative proportion of mitral/tufted cell adaptation that can be attributed to depression at the olfactory receptor neuron synapse needs to be addressed in future work using either sensors of synaptic vesicle release ( Bozza et al, 2004 ; Wachowiak et al, 2005 ) or glutamate targeted to postsynaptic neurons ( Marvin et al, 2013 , 2018 ; Moran et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 17, 2021. ; https://doi.org/10.1101/2021.09.15.460561 doi: bioRxiv preprint significant change in onset or peak latency (see Fig. 1G legend), the magnitude of the change in these experiments (<10 ms) was negligible compared to the range of onset and peak latencies seen across different glomeruli in the same preparation, which ranges over a span of 200 -250 ms (Moran et al, 2021). These results confirm that GABAB-mediated inhibition regulates the strength of glutamatergic signaling from presynaptic sources onto MT cells in vivo (McGann et al, 2005;Wachowiak et al, 2005;Brunert et al, 2016), and suggest that presynaptic inhibition contributes little to the inhalation-linked timing of these signals.…”
Section: Presynaptic Inhibition Does Not Impact Inhalation-linked Dynamics Of Glutamate Signalingmentioning
confidence: 80%
“…Potential OB circuit mechanisms for shaping MT cell output dynamics have been well-characterized using OB slice preparations, and include modulation of glutamate release from ET cells onto MT cells (Hayar et al, 2004a;De Saint Jan et al, 2009;Gire et al, 2012) as well as feedforward inhibition via several distinct inhibitory interneuron pathways (Murphy et al, 2005;Gire and Schoppa, 2009;Shao et al, 2012). In a recent study using glutamate and Ca 2+ imaging from the mouse OB in vivo (Moran et al, 2021), we found that glutamatergic signaling onto MT cells showed complex dynamics both within and across inhalations and that the slower temporal patterning was well-correlated with that of MT cell Ca 2+ signals, highlighting the importance of excitatory pathways in generating MT cell patterning.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations